2017
DOI: 10.1186/s13073-017-0407-3
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and TGF-β signalling cooperate to overcome MYCN-induced retinoid resistance

Abstract: BackgroundRetinoid therapy is widely employed in clinical oncology to differentiate malignant cells into their more benign counterparts. However, certain high-risk cohorts, such as patients with MYCN-amplified neuroblastoma, are innately resistant to retinoid therapy. Therefore, we employed a precision medicine approach to globally profile the retinoid signalling response and to determine how an excess of cellular MYCN antagonises these signalling events to prevent differentiation and confer resistance.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 115 publications
(149 reference statements)
2
42
0
1
Order By: Relevance
“…We found that a large subset of genes affected by GSK-J4 treatment was similarly affected by RA (Fig. 3A and table S7) (39). We confirmed that this gene overlap was statistically significant both through Fisher’s exact test and gene set enrichment analysis (GSEA) for both the RA up- and down-regulated gene sets (fig.…”
Section: Resultsmentioning
confidence: 97%
“…We found that a large subset of genes affected by GSK-J4 treatment was similarly affected by RA (Fig. 3A and table S7) (39). We confirmed that this gene overlap was statistically significant both through Fisher’s exact test and gene set enrichment analysis (GSEA) for both the RA up- and down-regulated gene sets (fig.…”
Section: Resultsmentioning
confidence: 97%
“…LMO4, CYP26A1, ASCL1, RET, FZD7 ve DKK1 genlerinin MYCN' nin artmış ekspresyonu ile tetiklenmesi ve TGF-β sinyal yolağını indüklemesi güncel bir retinoik asit direnç mekanizmasını tanımlamaktadır. 67 MYCN, mitokondriyal biyogenezi düzenleyen PPA, RGC1A, TFAM genlerinin ve mitokondriyal dinamikleri düzenleyen OPA1, MFN2, DRP1 genlerinin deregülasyonuyla apoptozu inhibe ederek, platin bileşiklerine karşı direnç açısından kritik farklı bir rol oynamaktadır. 68 Farklı yollarla gerçekleşen direnç mekanizmalarını belirleme çalışmaları hâlen devam etmektedir.…”
Section: Hedefe Yöneli̇k Tedavi̇ Yaklaşimi Ve Gelecek Perspekti̇flerunclassified
“…A novel retinoic acid resistance mechanism includes LIM domain only 4 (LMO4), cytochrome P450 family 26 subfamily A member 1 (CYP26A1), achaete-scute family BHLH transcription factor 1 (ASCL1), ret protooncogene (RET), frizzled class receptor 7 (FZD7), and dickkopf WNT signaling pathway inhibitor 1 (DKK1) genes are triggered by MYCN overexpression. These causes may lead to targeting of TGF-β signaling pathway, leading to resistance [67]. MYCN plays a different critical role in resistance to platinum compounds by inhibiting apoptosis through deregulation of PPARG coactivator 1 alpha (PPARGC1A), transcription factor A, mitochondrial (TFAM) genes regulating mitochondrial biogenesis and mitochondrial dynamin-like GTPase (OPA1), mitofusin 2 (MFN2), dynamin 1-like (DRP1) genes regulating mitochondrial dynamics [68].…”
Section: Targeted Treatment Approach and Future Perspectivesmentioning
confidence: 99%